Comparison of the response of a structure isolated from the base with a similar structure in a fixed form (Journal of Civil Engineering Researchers, 2026)
The seismic response characteristics of a 5-story isolated structure on the foundation surface and a non-isolated foundation with an equal number of indeterminate degrees and three types of design earthquakes have been investigated. The isolators were modeled using a mathematical model and elastic and hysteretic rotors, and significant results were obtained. The effect of the shape of the isolator force-deformation ring on the response of the isolated structure is studied under the variation of important system parameters such as the isolator yield displacement, superstructure flexibility, separation period, and the number of stories of the structure separated from the foundation. The changes of the upper story absolute acceleration and bearing displacement are calculated for different two-line systems under different earthquakes to study the effects of the isolator residual ring shape. The maximum displacement in the isolated structure is at the ground floor and is zero in the same structure without the isolator at the same location. The forces generated, shear and moment, are also less in the isolated state than in the fixed state to the foundation. Low values of isolator yield displacement (i.e., sliding-type isolator systems) tend to increase the superstructure accelerations associated with high frequencies. In addition, superstructure acceleration also increases with increasing superstructure flexibility.
Keywords: Base isolation; Earthquake; Displacement; Hysteresis; Equivalent linear